Green Open Space Planning Model for Parks at Pahlawan University - Adeswastoto, Hanantatur (Journal of Engineering Science and Technology Management, 2021)
Improving the quality of green space and efforts to improve the function of the area in the academic environment must be considered as an integral part of building arrangement activities. This is because the aspects of the building and the environment are inseparable components of settlements, supporting each other in a balanced, harmonious, and harmonious manner. As a campus that applies the concept of “Green Campus”, of course, it wants the quality of its environment to be well maintained even though it has the development of facilities and infrastructure, Universitas Pahlawan must of course also fulfill these provisions. Therefore, it is very necessary to model in planning the Park Green Open Space Planning Model at the Hero University with various considerations that are adapted to regional conditions, land area and benefits that can be enjoyed optimally by the academic community. Environmental Park planning model is carried out by reviewing based on spatial (spatial) and social aspects. The importance of the Environmental Park planning model is due to not applying an appropriate planning model so that direct utilization is not maximally felt by the academic community. This study examines more deeply the relationship between the spatial and social aspects of the environmental park